Acute and subacute toxicity evaluation of hydroalcoholic extract from the stem bark of Bois Bande (Parinari campestris Aubl.1772) in rats - Venkatesan Sundaram; Stephanie Mohammed; M. R. Srinivasan; Jenelle Johnson; Rod Suepaul; Indira Pargass; Chernell John; Danesha Ramdhanie; Shiann Lallack; Esther Daniel; Lester Gilkes (BMC, 2021)
Abstract Introduction The bark of Bois Bande (Parinari campestris) is a popular aphrodisiac in the Caribbean that has been traditionally used for many years to restore sexual vitality, increase sperm count, and treat erectile dysfunction, without valid scientific data. Acute and 28-day subacute toxicity studies were conducted to evaluate the safety of the hydroalcoholic extract of P.campestris bark and to find a safe dose for human use in conventional medicine. Methods The acute toxicity study used a single oral dose of P.campestris extract at four separate doses, 5, 50, 300, and 2,000 mg/kg, and was seen for 14 days, while the subacute toxicity study used a daily oral dose of P.campestris extract at 3 different doses, 100, 300, and 1000 mg/kg/day for 28 days. Results The LD50 of P.campestris extract was found to be greater than 2000 mg/kg in the acute toxicity study. P.campestris extract did not show toxicity at 1000 mg/kg/day in subacute toxicity trial; NOAEL was 1000 mg/kg/day in rats. However, the body weight was increased in males. Conclusion In conclusion, 1000 mg/kg P.campestris extract can be considered safe and non-toxic in males.